Autobiography and Confession: César González-Ruano’s Memories (Castilla. Estudios de Literatura, 2017)
César González-Ruano’s Memoirs present an interesting challenge for literary theory as a result of its putting into question the presuppositions of the autobiographical genre and, more specifically, the confessional one. Problems such as the multifaceted dispersion of the self, or the passage of time, which make all pretense of sincerity of the confession impossible, are studied in this article. In conclusion, the only possibility that the author faces when he writes his life is its absolute literaturization.
Keywords: autobiografphy; memoirs; confession; César González-Ruano